11-9x=38-16x

Simple and best practice solution for 11-9x=38-16x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-9x=38-16x equation:


Simplifying
11 + -9x = 38 + -16x

Solving
11 + -9x = 38 + -16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '16x' to each side of the equation.
11 + -9x + 16x = 38 + -16x + 16x

Combine like terms: -9x + 16x = 7x
11 + 7x = 38 + -16x + 16x

Combine like terms: -16x + 16x = 0
11 + 7x = 38 + 0
11 + 7x = 38

Add '-11' to each side of the equation.
11 + -11 + 7x = 38 + -11

Combine like terms: 11 + -11 = 0
0 + 7x = 38 + -11
7x = 38 + -11

Combine like terms: 38 + -11 = 27
7x = 27

Divide each side by '7'.
x = 3.857142857

Simplifying
x = 3.857142857

See similar equations:

| 2(x+7)=(2x-5) | | 0.34x-4.56=7.89 | | 4+1.6X=2.9X-12 | | (-2xy*2)(3x*2y*4)= | | 73-2x=4x+7 | | w+3w-48=0 | | 2-2x=14-8x | | 0.0625x+2.125=3 | | 375x-10x^2=0 | | w^3+10w-48=0 | | 10x+4=4(2x+1)-x+5 | | w^2+3w-48=0 | | w^2+10w-48=0 | | 68-3x=6x+24 | | 2x+x+x+9=x+2x+12 | | 7b+4=9b-2 | | -x+1+9x=-2+5x+18 | | -29-7x=9x-19 | | 6x+6+x=3+2x-17 | | 7+4x-3=9x+10-6x | | x+x+x+1=x+17 | | y=0.42x+19.26 | | 0.34x-2.71=1.28 | | 5a-3b=6c | | 6x-7=2x+12 | | 5z+17z=176 | | Z=-24 | | 3x+4y-2+x+5y+3=0 | | 6x+6+x=3+2x-7 | | 3m+27=57 | | m/9+10=16 | | 5x*3f= |

Equations solver categories